Fasciolosis in cattle and carabaos in selected barangays of Pikit and Kabacan, Cotabato, Philippines - Molina, Elizabeth C.; Navarra, Geraldson A.; Aloot, Paul O. (2010)
Two-hundred-eighty-on cattle and 225 carabaos were examined for the presence of eggs of Fasciola gigantica. Prevalence of the infection was assessed and its distribution with the age and sex of the animals determined. Fasciolosis was found to infect cattle and carabaos in the selected barangays. In both animals, the prevalence was significantly associated with age, with infection more commonly encountered in animals three years of age and older. Sex, however, did not influence the occurrence of the infection which was either weakly correlated (in cattle) or no correlation (in carabaos).
Keywords: Cattle; Water buffalo; Fasciolosis; Mindanao studies; Animal parasites